Size of the company as the main determinant of talent management in Slovakia - Radovan Savov; Drahoslav Lančarič; Jana Kozáková (Journal of Risk and Financial Management, 2020)
Nowadays, all sources in the reproduction process are easily substituted, thus the most important factors in reaching a competitive advantage are human resources. Talent management is the process oriented to enrich higher the ability of employers to increase their quality and productivity. Globalization has changed the structure of the companies in Slovakia, depending on the size of the company. This paper compares how the size of the company influences the main phases of the talent management process (strategy, identification, assessment, development, retaining). A scaled questionnaire was applied as a tool for data collection in 381 companies operating business in Slovakia. Questionnaire reliability was verified by Cronbach's alpha. To verify the existence of statistically significant differences between individual groups of respondents, ANOVA was used. We found that the main differences between small and large companies were identified in the phases of talent identification and talent development. In bigger companies, management is more focused on HR plans that include talent identification and acquisition and have more possibilities to develop talented individuals. On the other side we could see that small companies were more successful in the process of retaining the talents. Talented people in small companies are more loyal to the employers and stay in the company for longer periods than talented individuals in large companies.
Keywords: 330; management; performance; process; size of the company; talent